2011
DOI: 10.1519/jsc.0b013e3181ef64cb
|View full text |Cite
|
Sign up to set email alerts
|

V̇o2 Requirements of Boxing Exercises

Abstract: The purpose of this study was to quantify the physiological requirements of various boxing exercises such as sparring, pad work, and punching bag. Because it was not possible to measure the oxygen uptake (VO₂) of "true" sparring with a collecting gas valve in the face, we developed and validated a method to measure VO₂ of "true" sparring based on "postexercise" measurements. Nine experienced male amateur boxers (Mean ± SD: age = 22.0 ± 3.5 years, height = 176.0 ± 8.0 cm, weight = 71.4 ± 10.9 kg, number of figh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 8 publications
5
38
0
Order By: Relevance
“…The consequence of such high anaerobic participation was the accumulation of blood lactate, achieving in some cases values between 12 and 14 mmol/L (2). Even the specific conditioning exercises in training sessions revealed a high participation of the glycolytic system, in which regularly observed values were between 9 and 12 mmol/L in sparring and bag punching (12)(13)(14). The intermittent nature of this sport (three bouts of three minutes with one minute of rest) implied optimal recovery between bouts and conditioning to achieve the best performance during the rounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence of such high anaerobic participation was the accumulation of blood lactate, achieving in some cases values between 12 and 14 mmol/L (2). Even the specific conditioning exercises in training sessions revealed a high participation of the glycolytic system, in which regularly observed values were between 9 and 12 mmol/L in sparring and bag punching (12)(13)(14). The intermittent nature of this sport (three bouts of three minutes with one minute of rest) implied optimal recovery between bouts and conditioning to achieve the best performance during the rounds.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the perception of environment and the competition might constrain the values obtained. In a study that compared the same training session in two different conditions (in field and in laboratory), it was reported that boxers had greater values of HR and blood lactate concentrations in field (12). creased from round to round.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, athletes have been shown to exercise between 85-90% HR max 23 during simulated competition while blood lactate values of ~9-12 mmol have been reported following 3 24 rounds of sparring (1,11). In amateur boxing, upper-body power output (PO) is important as fast punches are 25 more likely to score points, in particular during the early stages of a fight (8).…”
Section: Introduction 1mentioning
confidence: 99%
“…Heart rate (HR) monitoring offers the opportunity to directly and easily evaluate the physiological profile of discipline-specific performance and inexpensively evaluate the physiological demands 5. However, few studies in the literature have reported on the physiological demands of combat sports 1,69. In this context, maximal graded exercise testing is commonly employed to determine physiological response to exercise.…”
Section: Introductionmentioning
confidence: 99%